SISTEM INFORMASI PERSEDIAAN BARANG PADA PONDOK BEKAM ABU HUDZAIFAH BEKASI - Irma Afrianti; Linda Marlinda; Emi Susilowati (LPPM STMIK ANTAR BANGSA, 2014)
Abstract— Pondok Bekam Abu Hudzaifah is a place in the fields of business services cupping and selling herbal medicines and islamic books .Of the more that it will be offered by the company offered the service for the satisfaction of their customers, both for the result of services provided and also for the inventorying system. The increasing activities in a the company means the more data and reports to be handled, one of which on data processing of the supplies or inventory .The number of data shall be procceed without the proper data processing’s techniques can be a problem, for example it was a data redudances or even lost the datas permanently. By using the Waterfall Method, writer mean to make and to design an inventory information system that can be reducing the system that is added to an inventory of goods in Pondok Bekam Abu Hudzaifah with using programming language Microsoft Visual Basic 6.0 and MySQL to more effectively and efficiently.